KREATIVITAS SERTA USAHA PARA GURU DI MADRASAH DINIYAH TAKMILIYAH AWALIYAH (MDTA) NURUL HASAN DALAM MEMBINA AKHLAK PARA SANTRI DI DESA KARANGGEBANG, JETIS, PONOROGO - Syah, Nur Aini (Institut Agama Islam Ngawi, 2024)
Abstract: It is very important to develop children's morals anywhere, whether in formal or informal institutions such as Madrasah Diniyah Takmiliyah Awaliyah (MDTA). The aim of this research is to find out what is the creativity of MDTA teachers is like and what efforts MDTA teachers make in developing children's morals in Karanggebang Village, Jetis, Ponorogo. This research is qualitative research. The methods used are observation, interviews and documentation. The data analysis uses qualitative descriptive analysis techniques. It means by describing the results of the data obtained in the research field. The subjects of this research are teachers, students and everything related to MDTA Nurul Hasan. The results of this research are the creativity carried out by MDTA teacher Nurul Hasan in the form of using varied learning methods. This can be seen from teachers using different ways and methods to develop children's morals. Some of the efforts made by MDTA teachers in developing morals are using exemplary methods, advice, habituation, giving gifts and giving punishment. Keywords: Creativity, Effort, Moral Development